Analytical solution of MHD free convective flow of couple stress fluid in an annulus with Hall and ion-slip effects - Srinivasacharya, Darbhashayanam; Kaladhar, Kolla (Nonlinear Analysis: Modelling and Control, 2011)
This paper presents the Hall and Ion-slip effects on electrically conducting couple stress fluid flow between two circular cylinders in the presence of a temperature dependent heat source. The governing non-linear partial differential equations are transformed into a system of ordinary differential equations using similarity transformations and then solved using homotopy analysis method (HAM). The effects of the magnetic parameter, Hall parameter, Ion-slip parameter and couple stress fluid parameter on velocity and temperature are discussed and shown graphically.